Aqueous composite binder for silicon-carbon negative electrode of lithium ion battery, preparation method of aqueous composite binder and battery containing aqueous composite binder

By developing an aqueous composite binder for silicon carbon anode of lithium-ion batteries, using guanidine bond-containing compounds, glutamic acid chain derivatives and polystyrene derivatives to form stable fibrous polymers, the shortcomings of lithium-ion battery binders in terms of cycle stability and rate performance are solved, and higher battery performance and longer service life are achieved.

CN119552593AActive Publication Date: 2025-03-04ZHENGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411809929.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-04
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing lithium-ion battery binders have shortcomings in improving battery cycle stability and rate performance, especially the volume expansion of silicon carbon anode material during charging and discharging, resulting in electrode breakage and interface unstable, and poor processing performance.

Method used

A water-based composite binder for silicon carbon anode of lithium-ion batteries is developed, including guanidine-containing compounds, glutamic acid chain derivatives and polystyrene derivatives, to form a stable fibrous polymer through hydrogen bonding of polar functional groups, enhancing the mechanical strength and electrical conductivity of the binder.

Benefits of technology

This water-based composite adhesive significantly improves the cycle stability and rate performance of lithium-ion batteries, reduces the volume expansion and crushing of the electrode, enhances the structural stability and ion conductivity of the electrode, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552593A_ABST
    Figure CN119552593A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a water-based composite binder for a silicon-carbon negative electrode of a lithium ion battery, a preparation method of the water-based composite binder and a battery containing the water-based composite binder. The water-based composite binder comprises the following three components: a first component which is a compound containing guanidine bonds and salts thereof; the second component is a chain derivative of glutamic acid; and the third component is a derivative of polystyrene. The composite binder suitable for the lithium ion battery silicon-carbon negative electrode is obtained, and the cycling stability and the rate capability can be improved. A chain derivative containing guanidine bonds and a chain derivative of glutamic acid are associated through hydrogen bonds to construct a polar functional group for inducing a solid and non-negative electrode solid electrolyte interface and a soft chain for buffering volume expansion. Meanwhile, the hard-chain polystyrene derivative containing the benzene ring provides a strong bonding effect for the composite binder. And the soft chain and the hard chain act simultaneously to wrap the silicon-carbon negative electrode, so that the volume expansion is greatly buffered. The water-based composite binder is simple and convenient to prepare, the raw materials are economical, and the water-based composite binder is green and environment-friendly by taking deionized water as a solvent. The aqueous composite binder can effectively improve the processability and the electrochemical performance of the silicon-carbon negative electrode of the lithium ion battery, and has a good commercial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to an aqueous composite binder for a silicon-carbon negative electrode of a lithium ion battery, a preparation method and a battery containing the binder. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, long service life and good low-temperature performance, and are considered to be one of the most promising new generation high-energy storage systems. Electrode materials, as a key component of lithium-ion storage, determine the cycle stability and energy density of the battery. Generally speaking, the electrode materials of lithium-ion batteries mainly include four parts: active materials, binders, conductive agents and current collectors. Although the binder occupies a very small proportion in the entire electrode system, it plays an important role in improving the electrochemical performance of the battery. The main function of the binder is to connect the active material, conductive agent and electrode current collector of the electrode to keep the electrode structure intact. Excellent binders promote the improvement of the battery's discharge platform and large current discharge capacity, reduce the internal resistance during low-rate charging, and improve the battery's fast charging ability. Silicon-carbon materials have become one of the most commercially promising negative electrode materials due to their high charging capacity, high safety and low cost, but they face problems such as large volume expansion during charging and discharging, unstable electrode / electrolyte interface caused by electrode fragmentation, and poor cycle performance, which restricts the large-scale commercial application of silicon-carbon negative electrode materials. In addition, due to the poor hydrophilicity of silicon-carbon materials, it is difficult to disperse evenly in water and the processing performance is poor.

[0003] At present, the most commonly used electrode binders are mainly oily polyvinylidene fluoride (PVDF) and aqueous carboxymethyl cellulose (CMC). As an oily binder, PVDF needs to use N-methylpyrrolidone (NMP), a toxic and expensive organic substance, as a solvent, which is not conducive to environmental protection and production cost control; at the same time, the HF bond mainly contained in PVDF is an inactive bond, so it cannot provide sufficient force to connect the electrode material, which is not conducive to the long-term cycle stability of the battery. As the most commonly used aqueous composite binder, CMC contains a large number of polar functional groups and has a good fixing effect on the electrode material, but it is relatively brittle, and the prepared silicon-carbon electrode is easy to lose powder and slag, which is not conducive to the long-term operation of the electrode. At the same time, its ionic conductivity needs to be improved.

[0004] Patent CN 106992299 A discloses a water-based binder, which is one or more of polyglutamic acid and / or its derivatives, and can also be a cellulose derivative, a sodium alginate derivative, and a polymer derivative. Compared with the organic solvent-based binder (PVDF), the water-based binder has no organic solvent release, has the characteristics of non-toxicity, low cost, non-flammability, and safe use, and has become an important development direction for lithium-ion battery binders. However, the problem with this patent is that both components are long-chain compounds, and their mechanical strength is relatively low, and its main component polyglutamic acid is more likely to form hydrogen bonds within the molecule rather than between molecules when used as a binder, making it difficult for the two components to produce synergistic effects and difficult to generate a stable SEI, which is the most important factor in inhibiting the expansion of silicon-based negative electrodes. Therefore, in view of the problems of the above-mentioned commonly used binders, it is very important to develop a new type of water-based composite binder with excellent performance. Summary of the invention

[0005] In view of the defects and shortcomings of existing lithium-ion battery binders, the present invention proposes an aqueous composite binder for lithium-ion battery silicon-carbon negative electrode, a preparation method and a battery containing the binder. The aqueous composite binder is applied to the silicon-carbon negative electrode of the lithium-ion battery, which effectively improves the cycle stability and rate performance of the battery.

[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] The present invention discloses an aqueous composite binder for a silicon-carbon negative electrode of a lithium-ion battery, wherein the aqueous composite binder comprises a first component, a second component and a third component. The first component is one or more compounds containing a guanidine bond or their salts as shown in Formula 1; the second component is one or two glutamic acid chain derivatives; and the third component is a derivative of polystyrene.

[0008]

[0009] In Formula 1, R1 is a straight chain or branched alkyl or alkoxy group having 1 to 10 atoms; R2 is -NH2, -COOH, -SO2-Ph-CH3, Any one of -CH3 and -H; R3 is any one of -NH2, -COOH and -H.

[0010] Preferably, the compound containing a guanidine bond is N-toluenesulfonyl-L-arginine or Nα-benzoyl-L-arginine; the salt of the compound containing a guanidine bond is L-arginine-L-pyroglutamate; and the glutamic acid chain derivative is one or two of L-glutamic acid polymer, N-(4-carbamoyl)-L-glutamic acid and L-γ-carboxyglutamic acid.

[0011] Its structural formula can be expressed as follows:

[0012]

[0013] Preferably, the polystyrene derivative is poly(sodium 4-styrene sulfonate), sodium polyanethole sulfonate or its derivatives. Preferably, the relative molecular mass of the first component is 200-500; the relative molecular mass of the L-glutamic acid polymer in the second component is 500,000-700,000, and the relative molecular mass of the remaining compounds is 200-500; the relative molecular mass of the third component is 100,000-300,000.

[0014] Preferably, the first component accounts for 30%-60% of the mass percentage of the water-based composite binder; the second component accounts for 20%-40% of the mass percentage of the water-based composite binder; the third component accounts for 20%-40% of the mass percentage of the water-based composite binder. The total mass percentage of the three components is 100%

[0015] The present invention also includes a method for preparing the above-mentioned water-based composite binder, the steps of which are as follows:

[0016] (1) stirring and dissolving the first component, the second component and the third component in deionized water to obtain a mixed solution;

[0017] (2) Drying the mixed solution to obtain a solid aqueous composite adhesive.

[0018] Preferably, the solvent is deionized water; the volume ratio of the total mass of the first component, the second component and the third component to deionized water is 0.1 g: (1-4) mL; the stirring temperature is room temperature (20-30° C.); and the time is 1-4 h.

[0019] The present invention also includes a lithium ion battery silicon-carbon negative electrode, which includes the aqueous composite binder, the silicon-carbon negative electrode material and a conductive agent.

[0020] Preferably, the conductive agent is any one of acetylene black, Ketjen black, carbon nanotubes, conductive carbon black and graphene; the silicon-carbon negative electrode material is a commercial silicon-carbon material. The mass ratio of the silicon-carbon negative electrode material, the conductive agent and the aqueous composite binder is (16-19): (1-2): (1-3). The mass ratio of the silicon-carbon negative electrode material, the conductive agent and the aqueous composite binder is (80-95): (5-10): (5-15), more preferably 80:10:10.

[0021] A method for preparing a lithium-ion battery silicon-carbon negative electrode sheet comprises the following steps:

[0022] (1) preparing a negative electrode slurry: adding a conductive agent, a silicon-carbon negative electrode material and the aqueous composite binder of the present invention according to a mass ratio, and then adding deionized water and stirring and mixing uniformly to obtain a negative electrode slurry;

[0023] (2) Preparation of lithium-ion battery silicon-carbon negative electrode sheet: The above negative electrode slurry is coated on the current collector and dried at 60-100° C. for 6-10 hours to obtain a lithium-ion battery silicon-carbon negative electrode sheet.

[0024] The invention also discloses a lithium ion battery, which comprises the lithium ion battery silicon-carbon negative electrode.

[0025] Beneficial effects of the present invention:

[0026] 1. The water-based composite binder provided by the present invention comprises one or more chain derivatives containing guanidine bonds, a second chain derivative of glutamic acid, and a third derivative of polystyrene. Through dissolution and heating reaction, the polar functional groups in the components react to form hydrogen bonds, forming a fibrous polymer rich in polar hydrophilic groups and more stable. The chain derivative containing guanidine bonds first combines with glutamic acid derivatives through hydrogen bonds to form soft chains, giving the composite binder rich polar amino and imino groups, and at the same time combines with oxygen-containing functional groups on the silicon-carbon surface to form hydrogen bonds, and wraps around the silicon-carbon surface to form a binder network. The hard-chain polystyrene derivative containing benzene rings can effectively resist the huge volume expansion of silicon-carbon materials during the electrochemical reaction process, and this method of applying both hard and soft chains can buffer the volume expansion of silicon-carbon negative electrodes to the greatest extent. At the same time, the compound containing guanidine bonds as the main component can provide ion conduction, and the cation stability formed after the H on the double bond N of guanidine leaves is very high. This unique structural network not only improves the dispersion of carbon materials in water, but also improves the structural stability and ion conductivity of silicon-carbon materials. The surface of the silicon-carbon negative electrode of the lithium-ion battery containing the binder is relatively flat, which reduces the excessive consumption of the electrolyte and the corresponding irreversible capacity loss, and improves the cycle stability of the lithium-ion battery. At the same time, the polar group can reduce the desolvation energy barrier, and the amino (-NH2) and carboxyl (-COO-) groups contained in L-glutamic acid can form coordination bonds with Li ions through sufficient electron donor ability, thereby improving the ionic conductivity of the polymer electrolyte and improving the kinetic properties.

[0027] 2. The first cycle coulombic efficiency of the lithium ion half-cell using the aqueous composite binder of the present invention is greater than 90%, and the specific capacity after 100 cycles can still reach 800 mAh / g.

[0028] 3. The lithium-ion battery using the aqueous composite binder of the present invention can effectively adsorb lithium ions, reduce the desolvation barrier of lithium ions, accelerate the desolvation process, and reduce the decomposition of organic solvents on the electrode surface, thereby forming a thinner SEI, because the binder covering the surface of the silicon-carbon electrode has a large number of strongly electronegative groups; it helps to maintain the stability of the interface, reduce the interface impedance, and improve the first efficiency, long cycle performance and rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is the infrared spectrum of the binder of Example 2.

[0031] Figure 2 The scanning electron microscope images are of the silicon-carbon negative electrode sheets prepared in Application Example 3 and Comparative Application Examples 1 and 2.

[0032] Figure 3 Transmission electron microscope images of the SEI of the silicon-carbon negative electrode sheets prepared in Application Example 3 and Comparative Application Examples 1 and 2 after the first week of discharge.

[0033] Figure 4 This is a comparison chart of the first-week charge and discharge curves of lithium-ion half-cells prepared using the silicon-carbon negative electrode sheets of Application Example 1 and Comparative Application Examples 1 and 2.

[0034] Figure 5 This is a comparison chart of the first-week charge and discharge curves of lithium-ion half-cells prepared using the silicon-carbon negative electrode sheets of Application Example 2 and Comparative Application Examples 1 and 2.

[0035] Figure 6 This is a comparison chart of the cycle performance of lithium-ion half-cells prepared using the silicon-carbon negative electrode sheets of Application Example 2 and Comparative Application Examples 1 and 2.

[0036] Figure 7 This is a comparison chart of the cycle performance of lithium-ion half-cells prepared using the silicon-carbon negative electrode sheets of Application Example 3 and Comparative Application Examples 1 and 2. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The weight of the relevant components mentioned in the embodiments of the present invention can not only refer to the specific content of each component, but also represent the proportional relationship of the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present invention is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present invention. Specifically, the weight described in the embodiments of the present invention can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0039] The molecular weight of PVDF used in the embodiments of the present invention and the comparative examples is 500,000, the molecular weight of CMC is 90,000, the average molecular weight of the third component is 100,000-300,000, the molecular weight of the L-glutamic acid polymer is 500,000-700,000, the relative molecular mass of L-arginine-L-pyroglutamate is 303, the relative molecular mass of N-(4-carbamoyl)-L-glutamic acid is 266, the relative molecular mass of L-γ-carboxyglutamic acid is 191, the relative molecular mass of Na-benzoyl-L-arginine is 278, and the molecular weight of N-toluenesulfonyl-L-arginine is 328. All of the above materials were purchased from Aladdin's official website.

[0040] Example 1

[0041] In this embodiment, a water-based composite adhesive is prepared, including 0.02 g of poly(sodium 4-styrene sulfonate), 0.02 g of L-glutamic acid polymer, 0.06 g of N-p-toluenesulfonyl-L-arginine and 2 mL of deionized water. The average molecular weight of poly(sodium 4-styrene sulfonate) is 300,000, and the molecular weight of L-glutamic acid polymer is 700,000. The preparation steps are as follows:

[0042] (1) Poly(sodium 4-styrene sulfonate), L-glutamic acid polymer and N-p-toluenesulfonyl-L-arginine are added to a sample bottle, dissolved in deionized water, stirred for 3 hours, and mixed evenly to obtain a mixed solution rich in polar functional groups.

[0043] (2) The mixed solution of step (1) is reacted and dried at 80° C. to obtain a water-based composite binder solid.

[0044] Example 2

[0045] In this embodiment, a water-based composite adhesive is prepared, including 0.03 g of sodium polyanethole sulfonate, 0.03 g of N-(4-carbamoyl)-L-glutamic acid, 0.04 g of L-arginine-L-pyroglutamate and 2 mL of deionized water. The molecular weight of sodium polyanethole sulfonate is 100,000. The preparation steps are as follows:

[0046] (1) Sodium polyanethole sulfonate, N-(4-carbamoyl)-L-glutamic acid and L-arginine-L-pyroglutamate are added into a sample bottle, dissolved with deionized water, stirred for 3 hours, and mixed evenly to obtain a mixed solution rich in polar functional groups.

[0047] (2) The mixed solution of step (1) is reacted and dried at 80° C. to obtain a water-based composite binder solid.

[0048] Example 3

[0049] In this embodiment, a water-based composite adhesive is prepared, including 0.03 g of poly(sodium 4-styrene sulfonate), 0.03 g of L-γ-carboxyglutamic acid, 0.04 g of Nα-benzoyl-L-arginine and 4 mL of deionized water, and the average molecular weight of poly(sodium 4-styrene sulfonate) is 200,000. The preparation steps are as follows:

[0050] (1) Poly(sodium 4-styrene sulfonate), L-γ-carboxyglutamic acid and Nα-benzoyl-L-arginine are added to a sample bottle, dissolved in deionized water, stirred for 3 hours, and mixed evenly to obtain a mixed solution rich in polar functional groups.

[0051] (2) The mixed solution of step (1) is reacted and dried at 60° C. to obtain a water-based composite binder solid.

[0052] Example 4

[0053] In this embodiment, a water-based composite adhesive is prepared, including 0.04 g of poly(sodium 4-styrene sulfonate), 0.03 g of L-glutamic acid polymer, and 0.03 g of Nα-benzoyl-L-arginine.

[0054] The average molecular weight of poly(sodium 4-styrene sulfonate) is 300,000; the average molecular weight of L-glutamic acid polymer is 500,000; the preparation steps are as follows:

[0055] (1) The poly(sodium 4-styrene sulfonate), polyglutamic acid and Nα-benzoyl-L-arginine are added into a sample bottle, 4 ml of deionized water is added to dissolve them, and the mixture is stirred for 3 hours. After mixing evenly, a mixed solution rich in polar functional groups is obtained.

[0056] (2) Drying the mixed solution of step (1) at 60° C. to obtain a water-based composite binder solid.

[0057] Application Examples 1-3

[0058] The aqueous composite binder solid, solvent water, and different electrode materials and conductive agents prepared in step (2) of Examples 1-3 are used to prepare lithium-ion battery silicon-carbon negative electrode sheets, respectively, corresponding to Application Examples 1-3, and the methods are as follows: the electrode material (silicon-carbon negative electrode material), conductive agent and binder are weighed and mixed in a mass ratio of 8:1:1, and then deionized water is added and stirred to mix evenly to prepare a battery sheet slurry; the battery sheet slurry is evenly coated on the current collector copper foil with a scraper, and dried in a forced air drying oven at 80°C for 8 hours to obtain a lithium-ion battery silicon-carbon negative electrode sheet.

[0059] The types and proportions of the electrode materials, conductive agents and aqueous composite binders used are shown in Table 1.

[0060] Table 1 Materials and ratios used in application examples 1-3 of lithium-ion battery silicon-carbon negative electrode plates

[0061]

[0062] Comparative application example 1

[0063] A lithium-ion battery silicon-carbon negative electrode sheet was prepared using PVDF as a binder and different solvents, electrode materials (silicon-carbon negative electrode materials) and a conductive agent. The method is as follows: the electrode material, the conductive agent and the binder are weighed and mixed evenly in a mass ratio of 8:1:1, and then NMP is added and stirred to mix evenly to prepare a battery sheet slurry; the battery sheet slurry is evenly coated on the current collector copper foil with a scraper, and dried in a forced air drying oven at 80°C for 8 hours to obtain a lithium-ion battery silicon-carbon negative electrode sheet.

[0064] Comparative Example 2

[0065] A lithium-ion battery silicon-carbon negative electrode sheet is prepared using CMC as a binder and different solvents, electrode materials (silicon-carbon negative electrode materials) and a conductive agent. The method is as follows: the electrode material, the conductive agent and the binder are weighed and mixed evenly in a mass ratio of 8:1:1, and then deionized water is added and stirred to mix evenly to prepare a battery sheet slurry; the battery sheet slurry is evenly coated on the current collector copper foil with a scraper, and dried in a forced air drying oven at 80°C for 8 hours to obtain a lithium-ion battery silicon-carbon negative electrode sheet.

[0066] The types and proportions of the conductive agent and the water-based composite binder are shown in Table 2.

[0067] Table 2 Comparative Application Example 1-2 Materials and Ratios of Silicon-Carbon Negative Electrode Plates for Lithium-Ion Batteries

[0068]

[0069] Implementation effect example

[0070] (1) The lithium-ion battery silicon-carbon negative electrode plates of Application Examples 1-3 and Comparative Application Examples 1-2 were assembled into button-type half-cells as follows: the prepared silicon-carbon negative electrode plates were punched into small discs with a diameter of 13 mm, and then the plates, diaphragms, electrolytes, lithium sheets, springs and gaskets were packaged with positive and negative electrode shells in a glove box filled with argon to obtain 2025 button-type half-cells, wherein the electrolyte was a commercial silicon-carbon negative electrode electrolyte purchased from Duoduo Reagent Network.

[0071] The constant current method was used to test the cycle stability and rate performance of each lithium-ion half-cell. The potential window was 0.01-1.5 V for the silicon-carbon negative electrode material and the current density was 360 mA / g. The test results are shown in Table 3.

[0072] Table 3 Lithium ion half-cell performance test results of application examples 1-3 and comparative application examples 1-2

[0073]

[0074] It can be seen from the data in Table 3 that the cycle stability of the lithium ion half-cells using the aqueous composite binder of the present invention in Application Examples 1-3 is generally high, and the specific capacity after a certain number of cycles is improved compared with the lithium ion half-cells of Comparative Application Examples 1 and 2, indicating that the aqueous composite binder prepared by the present invention is well suitable for the silicon-carbon negative electrode of lithium ion batteries and plays an important role in improving the performance of lithium ion batteries.

[0075] Figure 1 The infrared spectrum of the water-based composite binder of Example 2 shows that the hydrogen bonds at 3587 and 3362 are intramolecular; 2920, 2362, 1647, 1408 and 1160 cm -1 The characteristic peaks of -NH, CN and C=O, -OH, -COC bonds respectively indicate that this water-based composite binder has a variety of polar functional groups, and the peak at 3500cm -1 The left and right offset peaks correspond to the carboxyl group in the glutamic acid derivative forming a hydrogen bond with the amino group in the guanidine bond-containing derivative, and at the same time combining with the oxygen functional group on the silicon carbon surface to improve its dispersion, which helps to smooth the electrode and enhance the bonding effect on the electrode.

[0076] Figure 2 The scanning electron microscope (SEM) images of the silicon-carbon negative electrode sheets of Application Example 3 and Comparative Application Examples 1 and 2 show that there is obvious fibrous binder on the surface of the silicon-carbon negative electrode sheet of Application Example 3, indicating that the mixture of the binder and silicon carbon is more uniform, and the adhesion between the materials is tighter than that of Comparative Application Examples 1 and 2, which can reduce the contact between defects on the electrode and the electrolyte, thereby reducing excessive consumption of the electrolyte, and helping to improve the cycle stability of the battery.

[0077] Figure 3 The transmission electron microscope (TEM) images of the solid electrolyte membrane (SEI) of the silicon-carbon negative electrode plates of Application Example 3 and Comparative Application Examples 1 and 2 after the first week of discharge show that the use of the aqueous composite binder of the present invention induces the formation of a thinner SEI (92nm) on the electrode surface, while the SEI of Comparative Application Examples 1 and 2 is thicker. The thinner SEI indicates that the electrolyte consumption on the electrode surface is less, and the uniform interface helps to increase the transmission rate of lithium ions, thereby improving its kinetic characteristics and cycle stability. The thicker SEI indicates that the electrolyte will be over-consumed, which is not conducive to the rapid transmission of lithium ions and is more easily broken, resulting in lower cycle stability of the battery.

[0078] Figure 4 It is a comparison chart of the first-week charge and discharge curves of lithium-ion half-cells prepared using the silicon-carbon negative electrode sheets of Application Example 1 and Comparative Examples 1 and 2. Figure 5 The first week charge and discharge curve comparison diagram of lithium ion half-cells prepared by using silicon-carbon negative electrode sheets of application example 2 and comparative examples 1 and 2. Figure 4 , Figure 5 It can be seen that the silicon-carbon negative electrode using the aqueous composite binder of the present invention has a larger specific charge capacity, indicating that the irreversible capacity of the electrode is greatly reduced compared with the control ratio. For example, excessive consumption of electrolyte caused by surface defects is greatly reduced. At the same time, the overall polarization of the electrode is small, which is conducive to the long-cycle stability of the battery.

[0079] Figure 6 , 7 The comparison chart of the cycle performance of lithium-ion half-cells prepared using silicon-carbon negative electrode sheets of different application examples (application examples 2 and 3) and comparative application examples 1 and 2 shows that the silicon-carbon negative electrode using the aqueous composite binder of the present invention has higher specific capacity and cycle stability, and the excellent SEI induced by the binder is beneficial to the long cycle performance of the battery, indicating that the binder has a great effect on the cycle stability of the battery and other aspects.

[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An aqueous composite binder for a silicon-carbon negative electrode of a lithium-ion battery, characterized in that: The water-based composite binder comprises a first component, a second component and a third component; the first component is one or more guanidine bond-containing compounds or their salts as shown in Formula 1; the second component is one or two glutamic acid chain derivatives; and the third component is a polystyrene derivative. In Formula 1, R1 is a straight chain or branched alkyl or alkoxy group having 1 to 10 atoms; R2 is -NH2, -COOH, -SO2-Ph-CH3, Any one of -CH3 and -H; R3 is any one of -NH2, -COOH and -H.

2. The aqueous composite binder for lithium ion battery silicon-carbon negative electrode according to claim 1, characterized in that: The compound containing a guanidine bond is N-toluenesulfonyl-L-arginine or Na-benzoyl-L-arginine; the salt of the compound containing a guanidine bond is L-arginine-L-pyroglutamate.

3. The aqueous composite binder for lithium ion battery silicon-carbon negative electrode according to claim 1, characterized in that: The chain derivative of glutamic acid is one or two of L-glutamic acid polymer, N-(4-carbamoyl)-L-glutamic acid and L-γ-carboxyglutamic acid; the derivative of polystyrene is sodium poly(4-styrene sulfonate), sodium polyanethole sulfonate or its derivatives.

4. The aqueous composite binder for lithium ion battery silicon-carbon negative electrode according to claim 3, characterized in that: The relative molecular weight of the L-glutamic acid polymer is 500,000-700,000, and the average molecular weight of the third component is 100,000-300,000.

5. The aqueous composite binder for lithium ion battery silicon-carbon negative electrode according to claim 1, characterized in that: The mass fractions of the first component, the second component and the third component in the water-based composite binder are 30-60%, 20-40% and 20-40% respectively.

6. The method for preparing the aqueous composite binder for the silicon-carbon negative electrode of a lithium ion battery according to any one of claims 1 to 5, characterized in that: Here are the steps: (1) stirring and dissolving the first component, the second component and the third component in deionized water to obtain a mixed solution; (2) Drying the mixed solution to obtain a solid aqueous composite adhesive.

7. The method for preparing the aqueous composite binder for the silicon-carbon negative electrode of a lithium ion battery according to claim 5, characterized in that: The volume ratio of the total mass of the first component, the second component and the third component to deionized water is 0.1 g: (1-4) mL; the stirring temperature is 20-30° C.; and the stirring time is 1-4 h.

8. A lithium-ion battery silicon-carbon negative electrode, characterized in that: The lithium-ion battery silicon-carbon negative electrode comprises the aqueous composite binder for the lithium-ion battery silicon-carbon negative electrode according to any one of claims 1 to 5, a silicon-carbon negative electrode material and a conductive agent.

9. The lithium-ion battery silicon-carbon negative electrode according to claim 8, characterized in that: The mass ratio of the silicon-carbon negative electrode material, the conductive agent and the aqueous composite binder is (16-19):(1-2):(1-3); the conductive agent is any one of acetylene black, Ketjen black, carbon nanotubes, Super P and graphene; the silicon-carbon negative electrode material is a commercial silicon-carbon material.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery silicon-carbon negative electrode according to claim 8 or 9.

Citation Information

Patent Citations

  • Waterborne binder and lithium battery containing same

    CN106992299A

  • Water-based binder and application thereof in hard carbon negative electrode of sodium-ion battery

    CN118580804A

  • Binder for lithium secondary battery, and electrode and lithium secondary battery comprising the same

    KR1020170001129A